PERSEPSI WISATAWAN DALAM PENGEMBANGAN WISATA PENDIDIKAN BERBASIS KONSERVASI GAJAH SUMATERA (Elephas maximus sumatranus) (Perception Of Tourist Development Based Tourism Conservation Education Of Sumatran Elephant (Elephas maximus sumatra - Indra Gumay Febryano; Rusita Rusita (Graduate School Bogor Agricultural University (SPs IPB), 2018)
The perception of tourists is one of the most important aspects in the development of a tourist area, especially tourism that emphasizes the aspects of education and conservation. This study aims to find information on the perception of tourists in the development of conservation-based education tourism. The method used is survey method and the sample in this research is the tourists and related stakeholder in development. Determination of the number of samples in the population using Slovin formula, so the result at least 100 tourists. Data analysis is descriptively quantitative. The location of the study was conducted at the Elephant Conservation Center (PKG) Way Kambas National Park (TNWK). The results of interviews to 200 respondents known as 98% of respondents who come to PKG aims to travel elephants, 1% doing research and 1% work visit activities and other activities. Perceptions of elephant attractions are classified as Good (44%), 18% is not good. Besides, there were also perception study on service at Elephant Conservation Center (PKG), 53% stated good service, 53% stated facilities good enough, 55% said tourism tourism in PKG quite good, while 57% accessibility to tourism object is not good, and 90% agreed if in the PKG developed into educational tours bebasis konsevasi.Hasil this study is expected to be a reference for managers in developing PKG TNWK become one of the elephant conservation tourism destination in Lampung Province.